Number 18 (December 1988) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1988)
(December 1988) - Pit-Ridge Nest Construction and Spawning Behavior of Semotilus lumbee and Semotilus thoreauianus. By W.S. Wollcott and E.G. Maurakis, 2 pp. A Need for Clarification of the Concept of Nest Building Among Cyprinid Minnows. By W.S. Wollcott and E.G. Maurakis, 1 p. plus Curatorial Notes and News Notes.
Keywords: fishes; spawning; nest construction; smotilus lumbee; semotilus thoreauianus